Resistance of t(17;19)‐acute lymphoblastic leukemia cell lines to multiagents in induction therapy. (15th July 2019) - Watanabe, Atsushi; Inukai, Takeshi; Kagami, Keiko; Abe, Masako; Takagi, Masatoshi; Fukushima, Takashi; Fukushima, Hiroko; Nanmoku, Toru; Terui, Kiminori; Ito, Tatsuya; Toki, Tsutomu; Ito, Etsuro; et al.
Abstract: t(17;19)(q21‐q22;p13), responsible for TCF3‐HLF fusion, is a rare translocation in childhood B‐cell precursor acute lymphoblastic leukemia(BCP‐ALL). t(1;19)(q23;p13), producing TCF3‐PBX1 fusion, is a common translocation in childhood BCP‐ALL. Prognosis of t(17;19)‐ALL is extremely poor, while that of t(1;19)‐ALL has recently improved dramatically in intensified chemotherapy. In this study, TCF3‐HLF mRNA was detectable at a high level during induction therapy in a newly diagnosed t(17;19)‐ALL case, while TCF3‐PBX1 mRNA was undetectable at the end of induction therapy in most newly diagnosed t(1;19)‐ALL cases. Using 4 t(17;19)‐ALL and 16 t(1;19)‐ALL cell lines, drug response profiling was analyzed. t(17;19)‐ALL cell lines were found to be significantly more resistant to vincristine (VCR), daunorubicin (DNR), and prednisolone (Pred) than t(1;19)‐ALL cell lines. Sensitivities to three (Pred, VCR, andl ‐asparaginase [l ‐Asp]), four (Pred, VCR, l ‐Asp, and DNR) and five (Pred, VCR, l ‐Asp, DNR, and cyclophosphamide) agents, widely used in induction therapy, were significantly poorer for t(17;19)‐ALL cell lines than for t(1;19)‐ALL cell lines. Consistent with poor responses to VCR and DNR, gene and protein expression levels of P‐glycoprotein (P‐gp) were higher in t(17;19)‐ALL cell lines than in t(1;19)‐ALL cell lines. Inhibitors for P‐gp sensitized P‐gp‐positive t(17;19)‐ALL cell lines to VCR and DNR. Knockout of P‐gp by CRISPRCas9 overcame resistance to VCR and DNR in the P‐gp‐positive t(17;19)‐ALL cell line. A combination of cyclosporine A with DNR prolonged survival of NSG mice inoculated with P‐gp‐positive t(17;19)‐ALL cell line. These findings indicate involvement of P‐gp in resistance to VCR and DNR in Pgp positive t(17;19)‐ALL cell lines. In all four t(17;19)‐ALL cell lines, RAS pathway mutation was detected. Furthermore, among 16 t(1;19)‐ALL cell lines, multiagent resistance was usually observed in the cell lines with RAS pathway mutation in comparison to those without it, suggesting at least a partial involvement of RAS pathway mutation in multiagent resistance of t(17;19)‐ALL. Abstract : We demonstrated an involvement of P‐glycoprotein in resistance to vincristine and daunorubicin in two t(17;19)‐ALL cell lines. In all four t(17;19)‐ALL cell lines, RAS pathway mutation was detected. Furthermore, among 16 t(1;19)‐ALL cell lines, multiagent resistance was usually observed in the cell lines with RAS pathway mutation, suggesting at least a partial involvement of RAS pathway mutation in multiagent resistance of t(17;19)‐ALL.